PENGARUH MEDIA POWER POINT INTERAKTIF TERHADAP HASIL BELAJAR TEMATIK SISWA SD - Fauzatul Ma'rufah Rohmanurmeta (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2022)
Based on field observations, there are still many schools with low learning outcomes. Interactive Power Point media is a learning media designed by using hyperlink power point which can produce interactive media presentations to improve student learning outcomes. The purpose of this study was to determine the effect of interactive Power Point media on elementary students' thematic learning outcomes. This research is a type of associative research. The subjects in this study were conducted on fourth grade students of SDN 1 Jenangan, totaling 20 students for the 2020/2021 academic year. This research uses ex post facto research method. The data was collected by using questionnaires and thematic student learning outcomes documents. Before being used, the research was conducted to test the validity and reliability of the research instrument. The prerequisite tests used include validity and linearity tests. Data analysis was carried out by descriptive analysis, and simple regression to test the formulated hypothesis. Based on the results of using interactive power point media in learning, it shows a simple regression line which is expressed in the form of the equation Y=5,345+0,936X with a correlation coefficient of R=0,623. The existence of these equations shows that if the use of interactive power point learning media (x) has increased by one unit, the students' thematic learning outcomes (y) have increased by 0.936 units. Based on simple regression analysis, the t-count value was 9.014. While the t-table is 1.642 with a significance level of 5%. The t-count value is greater than the t-table value, so that the use of interactive power point learning media has a positive and significant influence on the thematic learning outcomes of elementary school students.